Pengaruh Geometri Jalan Terhadap Konsumsi Bahan Bakar pada Penambangan Batubara PT Bima Nusa Internasional Site PT Kideco Jaya Agung di Kecamatan Muara Komam, Kabupaten Paser, Provinsi Kalimantan Timur - Bagas Ghozi Adiwiyuga; Dudi Nasrudin Usman; Zaenal (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Bima Nusa Internasional is a contractor company engaged in the coal mining business which is located at the PT Kideco Jaya Agung site. Mining activities are carried out with an open pit mining system using a strip mining type. The use of diesel as a fuel has a significant effect on mining operational costs. There are several factors that can affect the use of fuel in mechanical devices, one of which is the road geometry. Therefore this research was conducted to increase the productivity of the dig-load and transport equipment with more efficient fuel consumption. Based on actual conditions in the field, there are still several road segments whose grade are not in accordance with the AASHTO standard is above 12%, so that the rimpull that must be overcome by the mechanical device is getting bigger, with the use of greater rimpull will make fuel consumption even greater which will have an impact on mining operational costs, so the company must evaluate the use of fuel in each work unit to reduce operational costs. Based on the results of observations and calculations in field observations, the actual production of conveyances equipment is 220,33 BCM/hour with an average fuel consumption conveyances equipment 14,82 liters/hour. The actual value of the fuel ratio in research activities for conveyances equipment means is 0,27 liters/BCM, and the fuel cost is Rp. 51.766.012 /month/tool. After conducting a study on road geometry, the production value increased to 257,64 BCM/hour/tool with a fuel ratio of 0,23 liter/BCM, and fuel cost to Rp. 44.273.822 /month/tool, so that after repairs decreased costs of Rp. 7.492.190 /month/tool. Improvements in road conditions greatly affect equipment production, fuel consumption, fuel ratio, and fuel cost so as to reduce operational costs in mining. Abstrak. PT Bima Nusa Internasional merupakan perusahaan kontraktor bergerak di bidang usaha pertambangan batubara yang berlokasi di site PT Kideco Jaya Agung. Penambangan dilakukan dengan Sistem Tambang Terbuka menggunakan jenis Strip Mining. Penggunaan solar sebagai bahan bakar memberikan pengaruh biaya operasional penambangan yang cukup besar. Terdapat beberapa faktor yang dapat mempengaruhi penggunaan bahan bakar pada alat mekanis, diantaranya kondisi geometri jalan. Oleh sebab itu penelitian ini dilakukan untuk meningkatkan produktivitas alat gali-muat dan angkut dengan penggunaan bahan bakar yang lebih efisien. Berdasarkan keadaan aktual di lapangan masih terdapat beberapa segmen jalan yang kemiringannya tidak sesuai dengan standar AASHTO yaitu di atas 12%, sehingga Rimpull yang harus diatasi oleh alat mekanis tersebut semakin besar, dengan penggunaan rimpull yang besar akan membuat konsumsi bahan bakar menjadi semakin besar yang akan berdampak pada biaya operasional penambangan, sehingga perusahaan harus mengevaluasi penggunaan bahan bakar di setiap unit kerja untuk menekan biaya operasional. Berdasarkan hasil pengamatan dan perhitungan pada kegiatan lapangan, produksi alat angkut aktual adalah 220,33 BCM/jam dengan rata-rata konsumsi bahan bakar alat 14,82 liter/jam. Nilai Fuel Ratio secara aktual pada kegiatan penelitian untuk alat angkut adalah 0,27 liter/BCM, serta Fuel Cost sebesar Rp. 51.766.012 /bulan/alat. Setelah dilakukan kajian pada geometri jalan, nilai produktivitas naik menjadi 257,64 BCM/jam dengan Fuel Ratio 0,23 liter/BCM, serta Fuel Cost menjadi Rp. 44.273.822 /bulan/alat, sehingga setelah perbaikan mengalami penurunan biaya sebesar Rp. 7.492.190 /bulan/alat. Perbaikan pada kondisi jalan berpengaruh terhadap produksi, konsumsi bahan bakar, Fuel Ratio, dan Fuel Cost sehingga dapat mengurangi biaya operasional pada penambangan.